Вы находитесь на странице: 1из 37

, ,

5 2013



.

, , .
, ,
,
[a, b], x = a
x = b, Ox.
y
y = f (x)

. :
.


Zb
f (x) dx.
a

a b (a ,
b ), f (x) .

, c


,
:
Zb
1
C dx = C(b a) (C ,
a

),
Zb
Zc
Zb
f (x) dx = f (x) dx + f (x) dx, a < c < b.
a

Zc
S1 =

Zb
f (x) dx, S2 =

Zb
f (x) dx, S1 + S2 =

f (x) dx
a

y = f (x)

S1

S2


f (x) < 0, a x b,
, :
Zb
f (x) dx = S.
a

y
a

b
x
S
y = f (x)


, .
Zb
f (x) dx = S1 S2 + S3 .
a

y
S1

S3

S2

, .
Z2
Za
Za
1
(a) x dx, (b) (a 2x) dx, (c) (kx + b) dx,
1

Za
2

a2 x 2 dx

a
Z

Za

x(2a x) dx,

sin x dx.

I
, f (x) [a, b].
[a, b] n a = x0 , x1 , . . . , xn = b.
mi = inf{f (x)|x [xi1 , xi ]}, Mi = sup{f (x)|x [xi1 , xi ]}.
y

x1

x2

x3

x4

II

( Jean Gaston Darboux


(18421917)):
Smin =

n
X

mi (xi xi1 ),

i=1

Smax =

n
X

Mi (xi xi1 ),

i=1

. ()
, () .

Smin Smax [a, b].

, Smin
, .

S = sup Smin ,

S = inf Smax ,

sup inf [a, b].


, S S.

S S , f (x)
[a, b],
f (x)
Zb
f (x) dx = S = S.
a

[a, b].
.
,
(Georg-Friedrich-Bernhard Riemann
(18261866)),
.
.

I
f (x) [a, b]
S = f (1 )(x1 x0 ) + + f (n )(xn xn1 ),

a = x0 < x1 < < xn1 < xn = b,


xk 1 < k < xk , k = 1, . . . , n.
( )
I =
lim
S,
max xk 0

Zb
f (x) dx = I =

lim

max xk 0

S.

(1)

II

(1) : > 0
> 0 max xk <
|I S| < .



Rb
f (x) dx a > b a = b.
a


Za

Zb
f (x)dx =

f (x)dx = 0
a

Za

f (x)dx.
b


a, b, c (
a < c < b). , a < b < c
Zb

Zc
f

f =
a

Zc

Zc
f =

Zb
f+

f.
c

f (x), [a, b],


, .

f (x) [a, b] (
). .
.
(
Johann Peter Gustav
Lejeune Dirichlet (18051859))
(
1, x
d(x) =
0, x
.

Zb

Zb
Cf (x) dx = C

f (x) dx
a

Zb

Zb
(f (x) + g(x)) dx =

Zb
f (x) dx +

g(x) dx
a

Zb
C dx = C(b a)

f (x) g(x), a x b,
Zb

Zb
f (x) dx

a
2

g(x) dx
a

. a < c < b
Zb

Zc
f (x) dx =

Zb
f (x) dx +

f (x) dx
c

f (x) [a, b] .
[a, b]
Zb
f (x) dx = f ()(b a).
a

f () f (x)
[a, b].

II

f (x) , g(x)
[a, b]. [a, b]
Zb

Zb
f (x)g(x) dx = f ()

g(x) dx.
a

f (x)
Zx
a.
f (t) dt
a

x.

0
x
Z
f (t) dt = f (x),
a


. ,
Zx

Z
f (x) dx =

f (t) dt + C.
a

(2)

I
F (x) =

Rx

f (t) dt.

a
x+x
Z

F (x) = F (x + x) F (x) =

f (t) dt
x

f (x + h)

y
y = f (t)

f (x)
F

F (x)
a

x+h

II

F (x) = f ()x, [x, x + x].


f (x) ,
F 0 (x) = lim

x0

F (x)
= lim f () = f (x).
x0
x


Z x
1
t 2 dt
0
Z x
2
2
et dt
0

2x

t dt


Z arcsin x
1
sin t dt
0
Z xp
3
2
x
t 2 1 dt
0
Z x
3
(x t) sin t dt
s0 Z
x

t dt


Z
y=

et dt

Zx
lim

t 2

dt =

.
2

0
2

d2
dx 2

(x t)f (t) dt = f (x).


0

f (x) [a, b], F (x)


.
Z
a

b

f (x) dx = F (b) F (a) = F (x)
a

(3)

f (x) [a, b] (t)


[, ].
Z

Zb
f (x) dx =
a

f ((t))0 (t) dt,

() = a, () = b,

(t) [a, b]
t [, ].

(4)


Zb

b Zb

u dv = uv v du

(5)